Evaluación cuantitativa del riesgo de entrada del virus de la gripe aviar altamente patógeno en la comunidad valenciana por importación de aves vivas - Sanchez-vizcaíno Rodríguez, J. M.; Sánchez-vizcaíno Buendía, F.; Lainez Andrés, M. (Revista Complutense de Ciencias Veterinarias, 2008)
The Region of Valencia has had many imports of live poultry from different countries that have had several outbreaks of Highly Pathogenic Bird flu during their history. The aim of this paper is to do a quantitative assessment of the risk of entry of HPAI in the Region of Valencia and its provinces due to the importation of live poultry, and identify the countries which entail a higher risk. The results indicate that Alicante is the province with more risk and Italy is the country that represents the greatest proportion of risk due to his imports. The probability to introduce the HPAI virus to the Region of Valencia due to life poultry imports is low.